Underutilized crops in the livelihoods, diets, and adaptation practices of smallholders in Sikasso and Ségou, Mali: Baseline results from the programme “Linking agrobiodiversity value chains, climate adaptation and nutrition: Empowering the poor to manage risk” - Bioversity International; Institut d’Economie Rurale (2020)
The programme “Linking agrobiodiversity value cahins, climate adaptation and nutrition: Empowering the poor to manage risk” funded by IFAD and the European Union from 2015 to 2018 aims to strenghten the capacities of farmers to manage risks associated with climate change, poor nutrition status, and economic disempowerment through agrobiodiversity-based solutions. Enhancing productivity and promoting use of nutritious and climate-hardy underutilized species is the core of the initiative, which is focusing on fonio, Bambara groundnut and native vegetables in six villages in Sikasso and Segou regions of Mali. The approach is two-prong, involving on one hand, targeted value chain interventions for fonio and Bambara groundnut, and on the other hand, exploratory work to prioritize native vegetables and other underutilized crops that can fill nutrition gaps in critical seasons. A holistic approach addressing multiple bottlenecks in supply and demand is being applied for fonio and Bambara groundnut, engaging consultation and participation of multiple stakeholders to ensure the interventions are pro-poor and gender-sensitive and to advocate for supportive policies.